INKLUSIVITAS DISABILITAS NETRA PERSPEKTIF AL-QUR’AN DAN HADIS;: Studi Implementatif di Yaketunis Yogyakarta - Ahmad Saerozi; Arif Friyadi; Oktari Kanus; Abdullah Abdullah (STAIN Majene, 2026)
This study aims to analyze the implementation of Qur’anic and Hadith values related to persons with visual disabilities at the Islamic Foundation for the Welfare of the Blind (Yaketunis) in Yogyakarta. The study is grounded in Islamic teachings that affirm the equality of human dignity without discrimination based on physical conditions. These values serve as the theological foundation for religious institutions in developing inclusive education and empowerment programs for persons with disabilities. This research employs a descriptive qualitative approach, with data collected through observation, in-depth interviews, and documentation. The research subjects include foundation leaders, educators, and visually impaired learners at Yaketunis. Data analysis is conducted by referring to thematic interpretations of the Qur’an and Hadith concerning disability, and is further strengthened by John Rawls’ theory of social justice, which emphasizes the importance of creating a just. The findings indicate that the implementation of Qur’anic and Hadith values at Yaketunis is reflected in four main aspects: (1) spiritual aspects through religious guidance that fosters worship awareness and spiritual resilience; (2) social aspects through strengthening ukhuwah values and enhancing social acceptance of persons with disabilities; (3) academic aspects through religious learning based on Braille, audio media, and oral methods; and (4) economic aspects through skills training and the management of productive zakat to promote independence. This implementation aligns with the Islamic principle of rahmatan lil-‘a>lami>n. The study concludes that Yaketunis has successfully integrated Qur’anic and Hadith values holistically into the educational and empowerment system for persons with visual disabilities, and thus has the potential to serve as a model for the development of inclusive and just Islamic education.